Design and evaluation of text-free map interfaces : a thesis presented in partial fulfilment of the requirements for the degree of Master of Information Technology at Massey University, Albany, New Zealand - Bao, Bojian (Massey University, 2016)
The aim of this research is to design and evaluate a text-free online map interface for illiterate people and non-local-language speakers. The use of online maps is developing rapidly and while a large majority of people are using these applications, there are many illiterate people who find them extremely difficult to use due to their inability to read the text on the maps. Symbols and audio are two methods that can be used to replace the reliance on traditional text. The research conducts two surveys to define the suitable symbol type and identify features for online map design; designs a set of text-free online map applications and finally, evaluates each designed map application based on a sample of 90 participants (Native English Speakers, non-English Speakers and Illiterate People). The results illustrate that illiterate people find it more difficult to use the online map application compared with literate people. Text-free online map interfaces are necessary to support illiterate people and the map that included both symbol and audio was the most suitable type of text-free online map.
Image removed from thesis for copyright reasons: Figure 22 (tile map), page 51.
Keywords: Digital maps; Map reading; Application program interfaces (Computer software); User interfaces (Computer systems); Human-computer interaction; Assistive computer technology; Illiterate people; Text-free online map; User interface design; Research Subject Categories::TECHNOLOGY::Information technology